The behaviour of a retaining wall under seismic excitation - Boudina, Tounsia; Bounouni, Sofiane; Rouabeh, Aicha; Allout, Naas (Technium Social Sciences Journal, 2023)
In this research, the different methods to calculate the earth pressures on a retaining wall were exposed, for different loading conditions, namely static and dynamic. The dynamic response of a retaining wall under seismic loading was also studied. The simulation is done using the finite element code PLAXIS. The response is expressed in terms of acceleration and displacement. When using numerical models to study this type of problem, two different entities can be identified. The first one corresponds to the materials and the consideration of their behavior. The second part corresponds to the type of loading imposed, i.e. the input signal.